Total Flavonoids in Caragana (TFC) Promotes Angiogenesis and Enhances Cerebral Perfusion in a Rat Model of Ischemic Stroke - He, Qiansong; Li, Shirong; Li, Lailai; Hu, Feiran; Weng, Ning; Fan, Xiaodi; Kuang, Shixiang (Frontiers in Neuroscience, 2018)
Previous studies have demonstrated that total flavonoid extracts fromCaragana sinica (TFC) exert multiple therapeutic effects, promote blood flow, and exhibit anti-inflammatory and antioxidant properties. The present study aimed to investigate whether TFC promotes angiogenesis and exerts neuroprotective effects in a rat model of transient middle cerebral artery occlusion (tMCAO). Male Wistar rats were subjected to tMCAO for 1.5h, followed by 24h of reperfusion. TFC (15, 30, 60mg/kg) was administered for 14 days. Evaluations of neurological function were performed following reperfusion, and infarct volumes were assessed in brain slices stained with 2,3,5-triphenyltetrazolium chloride (TTC). Our results indicated that TFC significantly attenuated cerebral infarct volume and neurological deficits following tMCAO. LaserDoppler, micro-PET/CT, and MRI analysesfurther demonstrated that TFC reduced infarct volume and enhanced cerebral blood flow in a dose-dependent manner, with the most significant effects occurring at a concentration of 60 mg/kg. Significant up-regulation of CD31, VEGF,Ang-1, HIF-1α, Dll4, and Notch1 expression was also observed in the experimental groups, relative to that in the vehicle group. In summary, the results of the present study indicate that TFC (15, 30, 60 mg/kg) attenuates neurological deficits, reduces infarct volume, and promotes angiogenesis following MCAO in a concentration-dependent manner, likely via increases in the expression of CD31, VEGF,Ang-1, HIF-1α, Dll4 and Notch1. Further studies are required to determine the clinical usefulness and potential mechanisms of TFC in patients with cerebral focal ischemic stroke.